Association of Epstein‐Barr virus infection with oral squamous cell carcinoma in a case–control study. (28th August 2014) - Acharya, Sulav; Ekalaksananan, Tipaya; Vatanasapt, Patravoot; Loyha, Kulchaya; Phusingha, Pensiri; Promthet, Supannee; Kongyingyoes, Bunkerd; Pientong, Chamsai
<x xml:space="preserve">Abstract</x> Background Besides the well‐known risk factors, Epstein‐Barr virus (EBV) might play a significant role in oral squamous cell carcinoma (OSCC). To explore the role of EBV in OSCC, the prevalence of EBV infection in oral exfoliated cells of OSCC cases and controls in northeastern Thailand was investigated, and the association of EBV in tumor lesion cells was further confirmed. Methods Oral exfoliated cells were collected from OSCC cases and non‐cancer controls. Cells from tumor lesions were taken from OSCC patients for further strong confirmation of the association of EBV with OSCC. EBV DNA was detected by polymerase chain reaction (PCR) using primers specific for EBV DNA polymerase. The EBV DNA positive samples were confirmed further by nested PCR. Results Epstein‐Barr virus was detected in the oral exfoliated cells of 45.05% of OSCC patients and 18.08% of the non‐cancer control (P < 0.001). Similarly, EBV was detected in 32.5% of the tumor lesions. Betel quid chewing was statistically significantly associated with EBV prevalence (OR = 2.08), whereas no association with tobacco smoking and alcohol consumption. Alcohol consumption and betel quid chewing were significantly associated with OSCC (OR = 3.05 and OR = 5.05, respectively), but tobacco smoking was not associated. Interestingly, EBV was significantly associated with OSCC (OR = 3.76). Conclusions Epstein‐Barr virus prevalence is associated with OSCC and seems to be enhanced by betel quid chewing, suggesting that EBV may, together with betel quid chewing, act as an important etiological risk factor of OSCC.